2010
DOI: 10.1063/1.3366461
|View full text |Cite
|
Sign up to set email alerts
|

The role of particle-particle interactions in bubbling gas-fluidized beds of Geldart A particles: A discrete particle study

Abstract: Discrete particle simulations are by now well established as an effective tool to study the mechanics of complex gas-solid flows in gas-fluidized beds. In this study, a state-of-the-art discrete particle model is used to explore the role of particle-particle interactions in bubbling gas-fluidized beds of Geldart A particles. We find that the particle-particle interactions, including inelastic particleparticle collision; inter-particle friction and slightly cohesive forces, only have a negligible effect on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…where 𝑚 is the mass of one nanoparticle [38,52]. The same type of equation is proposed in [53] However, the nanoparticles in motion also exerce a force −𝑛 (𝑭 + 𝑭 ) on the fluid, which undergoes a total driving force 𝑭 𝒅 due to the pressure gradient as well [38,53]. The force balance on the fluid is then given by…”
Section: Relative Velocitymentioning
confidence: 99%
“…where 𝑚 is the mass of one nanoparticle [38,52]. The same type of equation is proposed in [53] However, the nanoparticles in motion also exerce a force −𝑛 (𝑭 + 𝑭 ) on the fluid, which undergoes a total driving force 𝑭 𝒅 due to the pressure gradient as well [38,53]. The force balance on the fluid is then given by…”
Section: Relative Velocitymentioning
confidence: 99%
“…35 In contrast, the particle equations of motion do not require a computational grid, and a constant time step is used. As has been used for similar systems, the DPM time step is equal to 1 3 10 26 s. 11,15,36 The particle velocity is updated through a first-order integration scheme, which is in turn used to update the particle's position. In this DPM-CFD coupled approach, the simulation effectively advances in two steps.…”
Section: Model Descriptionmentioning
confidence: 99%
“…X N c p51 2F vdw;pl n pl (15) where n pl is the unit vector along the line of contact pointing from particle p to particle l, and N c represents the number of cohesive particle-particle and particle-wall interactions. As discussed above, the model chosen here to represent surface roughness can only be considered an approximation.…”
Section: Model Descriptionmentioning
confidence: 99%
See 1 more Smart Citation
“…One possible reason is that, for Geldart A particles, the effect of sub-grid scale structure on constitutive laws is more pronounced [13][14][15]. At the same time, recent studies based on both two-fluid model and discrete particle model have shown that particle-particle interactions, including inelastic collision, the inter-particle friction and slightly cohesive force, play a minor role in the hydrodynamics of bubbling fluidized beds of FCC particles [5,16,17]. Therefore, a sub-grid scale model for inter-phase drag force appears to be the key point.…”
Section: Introductionmentioning
confidence: 97%